Adaptive IIR filtering in signal processing and control - Regalia, Philip A. (Electrical engineering and electronics, 1995)
"This unique reference/text integrates rational approximation with adaptive filtering - providing viable, numerically reliable procedures for creating adaptive infinite impulse response (IIR) filters and addressing the choice of filter structure to adapt, algorithm design, and the approximation properties for each type of algorithm. It recasts the theory of adaptive IIR filters by concentrating on recursive lattice filters - freeing systems from the need for direct-form filters." "Generously illustrated, Adaptive IIR Filtering in Signal Processing and Control is a practical daily reference for electrical and electronics, optical, telecommunications, control, digital or signal processing, and computer engineers; filter designers; and computer scientists; as well as an invaluable text for upper-level undergraduate and graduate-level students studying adaptive IIR filtering and system identification."--BOOK JACKET.